(3GdeMGSHI GdMchejI (B/s - (3hOjGf, dDj eMeO YHO GdQMeGfs; (3GdMOQH, RgjQ s ((3YeGf(B: s (3OGQ GdHOGjI(B, s, 2010)
(3GdGWGQ GdacQj ddeMGSHI GdMchejI , GdehGRfI GdYGeI ddOhdI , GdQbGHI GdeGdjI GdYGeI, GdSjGSGJ GdeGdjI GdfbOjI h GdGSJbQGQ GdGbJUGOj , EYOGO GdehGRfI GdYGeI aj GdeedcI GdCQOfjI GdgGTejI , GdCSGdjH GdMOjKI dEYOGO GdehGRfI GdYGeI , GdfXGe GdeMGSHj GdMchej aj VhA GdJTQjYGJ GdCQOfjI , GdeYGdLI GdeMGSHjI ddEjQGOGJ h GdebHhVGJ GdCNQi , GdeMGSHI GdNJGejI aj GdhMOGJ GdMchejI , GdYdGbI Hjf GdeMGSHI GdbhejI h GdGbJUGO , GdefXeGJ GdOhdjI h GdeMGSHI GdMchejI (B.s
(3eQGLY U(B.329s
Keywords: (3GdeGdjIs; (3GdeMGSHIs; (3GdeMGSHI GdMchejIs; (3JObjb GdMSGHGJ GdMchejIs